Improving the accounting of value added tax in business entities - Djalilov Rahmonkul Hamidovich; Khusanov Asadbek Akbar ugli (THE INNOVATION ECONOMY, 2026)
This ssientifis artisle is based on the value added tax, its rlase in the tax system of our rerublis and foreign sountries, the status and nesessity of using tax benefits